Role of Ultrasound in Neurocritical Care - Bhatt, Rashmi; Khanna, Puneet (Journal of Neuroanaesthesiology and Critical Care, 2020)
Bedside point of care ultrasound has acquired an extremely significant role in diagnosis and management of neurocritical care, just as it has in other specialties. Easy availability and increasing expertise have allowed the intensivists to use it in a wide array of situations, such as confirming clinical findings as well as for interventional and prognostic purposes. At present, the clinical applications of ultrasonography (USG) in a neurosurgical patient include estimation of elevated intracranial pressure (ICP), assessment of cerebral blood flow (CBF) and velocities, diagnosis of intracranial mass lesion and midline shifts, and examination of pupils, apart from the systemic applications. Transcranial sonography has also found use in the diagnosis of the cerebral circulatory arrest. An increasing number of clinicians are now relying on the use of ultrasound in the neurointensive care unit for neurological as well as non-neurological indications. These uses include the diagnosis of shock, respiratory failure, deep vein thrombosis and performing bedside procedures.
Keywords: neurocritical care; subarachnoid hemorrhage; traumatic brain injury; bedside ultrasonography; transcranial doppler; intracranial pressure; regional blood flow